INTERNATIONAL RELATIONS OF CHUI REGION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Тhe influence of migration in country on the national composition is discussed. They say the reason is about moving from one country to another for economic reasons. It turns out national composition. the number of Russians, Ukrainians and other indigeneus nationalities has decreased. This may be due to the fact that these nationalities participated in the migration prosess or due to the fact that there are fewer relatives of them. Despite this, the Chui region demonstrates a multinational composition. We also know that the ethnic composition of the region remains multinational and diverse. This shows that the process of economic migration has not completely changed the ethnic composition of the region.
Keywords: Interethnic relations, Chui region, social, cultural, region studies.